Association between human papillomavirus infection and common sexually transmitted infections, and the clinical significance of different Mycoplasma subtypes - A, Disi; Bi, Hui; Zhang, Dai; Xiao, Bingbing (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Human papillomavirus (HPV) infection, especially persistent high-risk HPV, is associated with cervical cancer. Female reproductive tract microecological disorders and lower genital tract infections have been increasingly correlated with HPV infection and cervical lesions. Due to their common risk factors and transmission routes, coinfection with other sexually transmitted infections (STIs) has become a concern. Additionally, the clinical significance of Mycoplasma subtypes appear to vary. This study aimed to assess the correlations between common STIs and HPV infection, and to investigate the clinical significance of Mycoplasma subtypes. Methods We recruited 1,175 patients undergoing cervical cancer screening at the Peking University First Hospital gynecological clinic from March 2021 to February 2022 for vaginitis and cervicitis tests. They all received HPV genotyping and detection of STIs, and 749 of them underwent colposcopy and cervical biopsy. Results Aerobic vaginitis/desquamative inflammatory vaginitis and STIs (mainly single STIs) were found significantly more often in the HPV-positive group than in the HPV-negative group. Among patients with a single STI, rates of infection with herpes simplex virus type 2 or UP6 in the HPV-positive group were significantly higher than in the HPV-negative group (ORadj: 1.810, 95%CI: 1.211–2.705, P=0.004; ORadj: 11.032, 95%CI: 1.465–83.056, P=0.020, respectively). Discussion Through detailed Mycoplasma typing, a correlation was found between different Mycoplasma subtypes and HPV infection. These findings suggest that greater attention should be paid to detecting vaginal microecological disorders in those who are HPV-positive. Further, lower genital tract infections, including both vaginal infections and cervical STIs, are significantly more common among women who are HPV-positive and who thus require more thorough testing. Detailed typing and targeted treatment of Mycoplasma should become more routine in clinical practice.